PASAR TEMATIK PELITA SUKABUMI: STRATEGI MENGHIDUPKAN KEMBALI PASAR DENGAN METODE URBAN AKUPUNKTUR - Beatriks Meylika Bataric; Olga Nauli Komala (Jurusan Arsitektur dan Perencanaan, 2022)
Traditional markets are one of the most important parts of the city. Markets not only play an important role in the city's economy, but are also a social space for sellers, buyers and market participants. With the development of the more modern and digital age, modern markets and online shops have emerged, threatening the existence of increasingly abandoned traditional markets. The stigma of traditional markets as dirty, smelly, messy, and unsafe places, has led to fewer visitors and buyers coming to traditional markets. Pelita Market as the oldest and largest traditional market in Sukabumi City, is also affected by the shortage of visitors and the gradual loss of attractiveness in the community. Therefore, in order to revitalize the market as a commercial center and as a third space in society, a design strategy that can regain the image of the Pelita Market region is necessary. This study uses an urban acupuncture approach and a third place design method. Data was taken from primary data sources such as surveys and direct interviews, and secondary data sources were from literature, books, journals and the internet. The strategy to revive Pasar Pelita area is carried out with the scenario of